Peculiar Features of Nuclear Power and Steam and Gas Plant of Thermal Power Station - I. A. Bokoun (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2007)
The paper reveals peculiar features concerning of power generation at a nuclear power station and a steam and gas plant of a thermal power station. According to technical and economical indices a nuclear power station is at a disadvantage in relation to a steam and gas plant of a thermal power station.